ANALISIS YURIDIS IMPLEMENTASI ASAS LEGALITAS DAN EQUALITY BEFORE THE LAW DALAM UNDANG-UNDANG NARKOTIKA - Sunardi Riono; Haris (Universitas Muhammadiyah Malang, 2021)
This research will discuss about how the application of the principle of legality in Law No. 35 years old. 2009 regarding the regulation of the authority to arrest suspects in criminal acts of abuse and illicit trafficking of narcotics and narcotics precursors by Police Investigators, PPNS and BNN Investigators. This research is based on the type of normative juridical research. The results of the research show that Article 82 paragraph (2) should have originally only been up to the letter